FRI0136 Transition time to osteoporosis in patients with rheumatoid arthritis. (23rd January 2014) - Kim, H. J.; Hwang, J.; Ahn, J. K.; Park, E.-J.; Cha, H.-S.; Koh, E.-M.; Lee, J.
Abstract : Background: Rheumatoid arthritis (RA) is an independent risk factor for osteoporosis. Although bone mineral density (BMD) testing is routinely performed in patients with RA, the optimal interval between BMD tests remains undetermined. Objectives: The aim of this study was to evaluate the transition time to osteoporosis in RA patients with normal BMD and in those with osteopenia at baseline, and to estimate the optimal BMD testing interval. Methods: We retrospectively analyzed 548 consecutive RA patients at a single tertiary hospital who underwent BMD testing on two or more occasions during October 1994 and December 2011. Patients were sorted into 5 groups; normal baseline BMD (T score, -1.00 or higher), mild osteopenia (T score, -1.01 to -1.49), moderate osteopenia (T score, -1.50 to -1.99), severe osteopenia (T score, -2.00 to -2.49) or osteoporosis (T score -2.50 or lower). The transition time to osteoporosis was defined as the estimated time for 10% of patients to make the transition to osteoporosis from normal BMD or from each subgroup of osteopenia. Risk factors for osteoporosis on initial BMD test were also assessed. Results: Patients were mostly women (96.4%) and the mean age was 55.6 ± 10.6 years. The mean follow-up duration of RA was 8.8 ± 4.3 years. At initial visit, 9.1% of patients had a past history of steroid use for diseases other than RA. Rheumatoid factor was positive in 330 of 531 patients (62.1%) and anti-CCP antibodies in 138 of 206 patients (67%). The mean duration between the initial visit and the first BMD screening was 32.7 ± 40.2 months and the prevalence of osteoporosis was 31.7% at screening (95% confidence interval (CI) 27.6 to 36.1). Estimated transition time to osteoporosis was 72 months (95% CI 36 to 90) for patients with normal BMD, 62 months (95% CI 28 to 126) for patients with mild osteopenia, 34 months (95% CI 16 to 60) for patients with moderate osteopenia, and 17 months (95% CI 10 to 21) for patients with severe osteopenia. The adjusted odds ratio (OR) for osteoporosis at initial BMD testing was high for older age (OR 1.066, 95% CI 1.029 to 1.105, p < 0.0001), past steroid use (OR 2.033, 95% CI 1.174 to 3.520, p = 0.0159), and current steroid use (OR 3.987, 95% CI 2.092 to 7.597, p < 0.0001). Conclusions: Our data indicate that osteoporosis would develop in less than 10% of RA patients within 6 years for patients with normal bone density, 5 years for patients with mild osteopenia, 2.5 years for patient with moderate osteopenia, and 1 year for patients with advanced osteopenia at baseline. Therefore, the interval for rescreening BMD testing should be adjusted based on the initial BMD result in patients with RA. Disclosure of Interest: None Declared